2014
DOI: 10.1002/tea.21139
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluations of elementary science programs: A best-evidence synthesis

Abstract: This article presents a systematic review of research on the achievement outcomes of all types of approaches to teaching science in elementary schools. Study inclusion criteria included use of randomized or matched control groups, a study duration of at least 4 weeks, and use of achievement measures independent of the experimental treatment. A total of 23 studies met these criteria. Among studies evaluating inquiry‐based teaching approaches, programs that used science kits did not show positive outcomes on sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 51 publications
(81 reference statements)
5
102
1
Order By: Relevance
“…Similar results were obtained in a bestevidence synthesis of elementary science programs by Slavin, Lake, Hanley, and Thurston (2014) who stated that: "science teaching methods focused on enhancing teachers' classroom instruction throughout the year, such as cooperative learning and science-reading integration, as well as approaches that give teachers technology tools to enhance instruction, have significant potential to improve science learning" (p. 901). In short, there is overwhelming evidence that cooperative learning as a pedagogical practice has had a profound effect on student learning and socialization (Slavin, 2014).…”
Section: Background Research On Cooperative Learningsupporting
confidence: 66%
“…Similar results were obtained in a bestevidence synthesis of elementary science programs by Slavin, Lake, Hanley, and Thurston (2014) who stated that: "science teaching methods focused on enhancing teachers' classroom instruction throughout the year, such as cooperative learning and science-reading integration, as well as approaches that give teachers technology tools to enhance instruction, have significant potential to improve science learning" (p. 901). In short, there is overwhelming evidence that cooperative learning as a pedagogical practice has had a profound effect on student learning and socialization (Slavin, 2014).…”
Section: Background Research On Cooperative Learningsupporting
confidence: 66%
“…"Any singled-authored account is necessarily selective and idiosyncratic" [19] and consequently four people were involved in this coding. The analysis was crosschecked and harmonized three times as it expanded, following the practice of previous reviewers [20,21].…”
Section: Coding the Text Samplementioning
confidence: 99%
“…Kit-based science programs have been in circulation since the 1960's (Jones, Robertson, Gardner, Dotger & Blanchard, 2012) and have shown to have a positive impact on student achievement (Young & Lee, 2005;Dickerson et al, 2006), student attitudes toward science (Kelly & Staver, 2005;Houston, Fraser & Ledbetter, 2008), and provides teachers with tools to enhance science learning (Robardey, Allard & Brown, 1994;Slavin, Lake, Hanley & Thurston, 2014). Some widely used kits include FOSS, which were first developed in the late 1980's and pilot tested in San Francisco.…”
Section: Kit-based Science Programsmentioning
confidence: 99%
“…In many districts is clear that current resources and materials are insufficient in providing students high-quality science instruction aligned to the NGSS. Improving science instruction at the elementary level will require districts to support teachers' content knowledge, limited amount of instructional time, and provide appropriate resources (Slavin et al, 2014). A best-evidence synthesis on elementary science programs by Slavin et al (2014) revealed mixed results in regard to kit-based implementation but does provide important considerations.…”
Section: Kit-based Science Programsmentioning
confidence: 99%
See 1 more Smart Citation